Electron transfer in an acidophilic bacterium: interaction between a diheme cytochrome and a cupredoxin. Issue 21 (11th May 2018) - Wang, X.; Roger, M.; Clément, R.; Lecomte, S.; Biaso, F.; Abriata, L. A.; Mansuelle, P.; Mazurenko, I.; Giudici-Orticoni, M. T.; Lojou, E.; Ilbert, M.
Abstract : Electrochemical studies of diheme cytochrome/cupredoxin complexes provide new insights into the electron transfer pathway in an acidophilic bacterium. Abstract : Acidithiobacillus ferrooxidans, a chemolithoautotrophic Gram-negative bacterium, has a remarkable ability to obtain energy from ferrous iron oxidation at pH 2. Several metalloproteins have been described as being involved in this respiratory chain coupling iron oxidation with oxygen reduction. However, their properties and physiological functions remain largely unknown, preventing a clear understanding of the global mechanism. In this work, we focus on two metalloproteins of this respiratory pathway, a diheme cytochrome c4 (Cyt c4 ) and a green copper protein (AcoP) of unknown function. We first demonstrate the formation of a complex between these two purified proteins, which allows homogeneous intermolecular electron-transfer in solution. We then mimic the physiological interaction between the two partners by replacing one at a time with electrodes displaying different chemical functionalities. From the electrochemical behavior of individual proteins, we show that, while electron transfer on AcoP requires weak electrostatic interaction, electron transfer on Cyt c4 tolerates different charge and hydrophobicity conditions, suggesting a pivotal role of this protein in the metabolic chain. The electrochemical study of the proteins incubated together demonstrates an intermolecular electron transfer involving the protein complex, in which AcoP is reduced through the high potential heme of Cyt c4 . Modelling of the electrochemical signals at different scan rates allows us to estimate the rate constant of this intermolecular electron transfer in the range of a few s −1 . Possible routes for electron transfer in the acidophilic bacterium are deduced.